Pengaruh penerapan model pembelajaran inkuiri terbimbing berbantuan metode pictorial riddle terhadap pencapaian kompetensi fisika siswa pada materi gerak lengkung di kelas X SMAN 1 Sutera - Gusriadi Putra; Djusmaini Djamas; syafriani syafriani (PILLAR OF PHYSICS EDUCATION, 2020)
Learning based on curriculum 2013 is still not applied by teachers and teachers has not yet varied the learning model used so as to impact on low learning outcomes. The study aims to determine how the implementation of the Learning Inquiry Model is assisted by the Pictorial method of Riddle with the learning outcomes of students ' physics. This type of research is a pseudo-experimental study with the design of Posttest Only Control Group Design. A knowledge aspect assessment instrument in the form of posttest and skill aspect. Data analysis techniques use descriptive statistical techniques. Testing homogeneity obtained by the results that both classes have the value of GIS homogeneity to the results of learning teaching Inkuiri assisted by Pictorial method Riddle of 0.422 with significance value 0.05. So the distributed research data is normal. The hypothesis test results were obtained a probability value of 0.000 so that H0 was rejected and H1 received study of the students ' arch motion in an experimental class using the learning Inquisitors guided by the aid of a higher riddle pictorial method Compared to the control class that uses the inquiry learning model is guided. The average grade of an experiment class is 80.17 and the average value of the control class is 75.57. It can therefore be concluded that there is a significant influence on the application of learning model of the Inquisies guided by a method of pictorial riddle towards the improvement of physics competence of grade X students at SMAN 1 Sutera.